The Importance of Social Capital in the Development of Religion Among University’s Students: A Case Study from Pakistan - Muhammad Asad Latif (LECTURES: Journal of Islamic and Education Studies, 2024)
Participation in congregational gatherings serves as a reflection of a person's religiosity. Such involvement promotes the creation of social capital. Family, friends, and neighborhood informal networks are significant producers of social capital and excellent venues for spreading religious ideas. Social capital and religion derive from the same roots. The current study investigates how social capital influences young people's religious development. Purposive sampling was used in the qualitative investigation. The sample consists of educated young women from Bahawalpur, Pakistan. From a place of learning, 25 in-depth interviews and 5 focus group discussions were done. Themes and narratives were used to analyze the data. The results imply that culture, environment, and family play significant roles in the development of religion. In conclusion, religious traditions have lost their essence and are becoming more and more materialistic.